ANALISIS HUKUM TENTANG SENGKETA TANAH YANG BERSERTIFIKAT DI TELUK MUTIARA KABUPATEN ALOR - PO Tausbele, Harun Hermon; Hedewata, Agustinus; Nubatonis, Orpa J (Petitum Law Journal, 2024)
Now in practice there are often fake certificates or double certificates in the community, so that land rights holders need to find information about the truth of physical data and juridical data on the land in question at the Local Land Office. Based on this case, the researcher formulated the main problems, namely: (1) How is the legal force of land that already has a certificate of ownership? (2) How is the settlement of land disputes certified? This study uses empirical legal research methods that examine how the law works in society. Aspects of the study examined the legal strength of the land that already has a certificate of property rights and Land Dispute Resolution certified. The results found that: (1) the legal certainty of the certificate containing the written provisions stated in the law or other regulations is absolute meaning it can not be contested. (2) Dispute Settlement can be done through three ways, namely: settlement through the judiciary, which is submitted to the General Court body in a civil manner, advocacy, through arbitration.